2015
DOI: 10.1002/2015jb012265
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing induced seismicity from natural seismicity in Ohio: Demonstrating the utility of waveform template matching

Abstract: This study investigated the utility of multistation waveform cross correlation to help discern induced seismicity. Template matching was applied to all Ohio earthquakes cataloged since the arrival of nearby EarthScope TA stations in late 2010. Earthquakes that were within 5 km of fluid injection activities in regions that lacked previously documented seismicity were found to be swarmy. Moreover, the larger number of events produced by template matching for these swarmy sequences made it easier to establish mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
108
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(118 citation statements)
references
References 23 publications
10
108
0
Order By: Relevance
“…This indicates that larger sequences do show some buildup of larger events. Together with the delay from initiation to maximum activity, this supports the notion that pure main shock‐aftershock sequences are rare among induced seismicity sequences (Skoumal et al, ) and that the seismic activity increases over time rather than decays as observed for clusters in Southern California (Vidale & Shearer, ). We explore the rise and decay of activity in section 3.4.…”
Section: Resultssupporting
confidence: 78%
“…This indicates that larger sequences do show some buildup of larger events. Together with the delay from initiation to maximum activity, this supports the notion that pure main shock‐aftershock sequences are rare among induced seismicity sequences (Skoumal et al, ) and that the seismic activity increases over time rather than decays as observed for clusters in Southern California (Vidale & Shearer, ). We explore the rise and decay of activity in section 3.4.…”
Section: Resultssupporting
confidence: 78%
“…We also note that the CLS earthquakes tend to cluster into distinguishable sequences or swarms (Figure ), which have been argued as a characteristic of induced seismicity in general [ Skoumal et al ., , ]. We interpret the swarminess in the CLS as a consequence of repeatedly stimulating the same fault to failure conditions [ Goertz‐Allmann and Wiemer , ] via pore pressure increase [ Kummerow et al ., ] during fluid injection into overpressured, low‐permeability rocks [ Cox , ].…”
Section: Discussionsupporting
confidence: 78%
“…Individual case examples of HF‐induced seismicity have been now be identified in Alberta (e.g., Wang et al, ), Arkansas (Yoon et al, ), British Columbia (e.g., B.C. Oil and Gas Commission, ), California (Kanamori & Hauksson, ), China (e.g., Lei et al, ), England (Clarke et al, ), Ohio (e.g., Skoumal et al, ), Oklahoma (e.g., Holland, ), Pennsylvania (Skoumal et al, ), and West Virginia (Skoumal et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Since these interpretations were made, larger‐magnitude earthquakes that have been attributed to hydraulic fracturing have occurred, including the 2015 M 4.6 earthquake in British Columbia, Canada (Atkinson et al, ; Mahani et al, ), and the 2016 M 4.7 earthquake in the Sichuan Basin, China (Lei et al, ). Additionally, while the number of cases identified prior to these studies was limited (Clarke et al, ; Darold et al, ; Friberg et al, ; Holland, ), more recent studies have found a higher prevalence of HF‐induced seismicity than would have been previously expected (Atkinson et al, ; Skoumal et al, ).…”
Section: Introductionmentioning
confidence: 99%